HUBUNGAN POWER OTOT LENGAN BAHU DAN KOORDINASI MATA DAN TANGAN DENGAN KETEPATAN SERVIS PADA SISWA EKSTRAKURIKULER BOLAVOLI SMP NEGERI 5 PEKANBARU - Rizky Rizaldo; Ramadi Ramadi; Ardiah juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The game of volleyball is one of the game's complex that is not easily done by any person, as in a game of volleyball required coordination of motion that is truly dependable movement to do all that is in the the game of volleyball. In the construction achievements in the game of volleyball is inseparable from the influence of the physical condition, mental, tactics, and techniques. Servicing one of the techniques in the game of volleyball. The service was one of the first blows to start the game volleyball is done by way of standing behind the end line and between the extension of the line side. Good service is a service that directly produces the figures or not acceptable. The purpose of this research is to know the relationship of power and coordination of arm muscles of the eyes and hands together against the accuracy of services over player volleyball. This research was carried out in volleyball field of Junior High School 5 Pekanbaru on January 2017- May 2018. Type of this research is quantitative research using design research korelasional, aims to find out the relationship between the free variables and bound variables based on the magnitude of the koefesien correlation. Research on data collection instruments this is a test service, test an explosive arm muscles using the Medicine ball, and Eye-hand Coordination test of [throw catch tennis balls]. These studies only take son students extracurricular volleyball that totalling 12 people and without the daughter student's extracurricular activities. The results of the tests the ability of the power arm and shoulder muscles having done the calculations generated Lcount 0.209, coordination of eye and hand Lcount 0127, tests the ability of Lcount services and Ltable of 0.192 and 0.242. This means that Lcount is smaller than Ltable. It can be concluded the spread data is Gaussian. Based on the analysis of the test t generate Rcount of 1.34. Then, there is the relationship power arm and shoulder muscles (X1) and the coordination of eye and hand (X 2) with the capability of servicing (Y) according to t-test analysis produces a Rcount of 0.80. From the analysis results can be concluded that there is a relationship of power arm and shoulder muscles (X1) and the coordination of eye and hand (X2) with the capability of servicing (Y) On Extracurricular volleyball Students of Junior High School 5 Pekanbaru.Key Words: Development, LKPD, Scientific Approach, Critical Thinking, World of Plants (Plantae)JOM